Unethical behavior at work : perception of frequency of occurrence and tolerance of misconduct in companies in Portugal - Swiatkiewicz, Olgierd (2012)
In this paper we present and discuss the problem of unethical behavior at workplace. Firstly, we clarify and distinguish notions of unethical and improper behavior, and how they change when we move from an organizational to a societal point of view. Secondly, we present a literature review on the topic of unethical/improper behavior at work. The main part of the text focuses on results of an empirical study on perception of frequency of occurrence and tolerance of a set of different types of unethical behavior. The results come from a survey carried out in Portugal on convenience sample. Using exploratory factor analysis we get three factors which explain 52% of the result variance of perception frequency and seven factors, from which two were retained, which explain 26% of the result variance of tolerance frequency. The factors demonstrated correlations with some independent (individual and institutional) variables (sex; age; level of education; tenure; hierarchical level; actual and future sense of security of employment and career development; property and capital origin of the company; its size, age, sector and financial situation). We underline that among other the two factors of tolerance are positively correlated with the level of education of respondents.